2016
DOI: 10.3390/infrastructures1010003
|View full text |Cite
|
Sign up to set email alerts
|

CFD Evaluation of Philippine Detached Structure with Different Roofing Designs

Abstract: The Philippines is located in the typhoon belt region in the western side of the Pacific Ocean. Every year, an average of twenty typhoons pass through the country, resulting in the loss of life and property. As the design of the roofing is an important factor in the structural integrity of the detached structures and the survival of the occupants, an evaluation of different roofing designs for the detached structure is needed. Different roofing designs, typical in Philippine detached structures were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Previous studies show that it is very important to do parametric studies of the computational grid [24][25][26]. Hence, this study conducted several parametric studies before deciding to use the computational grid as we did in our previous studies [17]. Figure 4a shows the wind velocity at different heights.…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies show that it is very important to do parametric studies of the computational grid [24][25][26]. Hence, this study conducted several parametric studies before deciding to use the computational grid as we did in our previous studies [17]. Figure 4a shows the wind velocity at different heights.…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%
“…Figure 3 shows the computational model preparation utilized in this study. It shows the computational domain, boundary conditions, and computational grid generated using the very fine and unstructured mesh with five layers [17]. The modeling and configuration of the computational domain for the present study is shown in Figure 4.…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations